Inhibition of eIF2α Phosphorylation by Peste des Petits Ruminant Virus Phosphoprotein Facilitates Viral Replication - Alfred, Niyokwishimira; Qian, Bang; Qin, Xiaodong; Yin, Xiangping; Prajapati, Meera; Dou, Yongxi; Li, Yanmin; Zhang, Zhidong (Frontiers in Veterinary Science, 2021)
Peste des petits ruminant virus (PPRV) causes a highly contagious disease in small ruminants. The molecular mechanism of PPRV replication and its interactions with hosts are poorly studied. In other paramyxoviruses, the viral phosphoprotein (P) has been associated with multiple functions for key biological processes such as the regulation of transcription, translation and the control of cell cycle. Phosphorylation of the α subunit of eukaryotic initiation factor 2 (eIF2α) is an important process for genes regulation in host cells under stress, including viral infection. In the present study, molecular mechanisms associated with PPRV replication and viral interaction with host cells were investigated. We describe the ability of PPRV to dephosphorylate eIF2α and the potentiality of PPRV P protein to induce the host cellular growth arrest DNA damage protein (GADD34) which is known to be associated with eIF2α dephosphorylation. Further, we observed that PPRV P protein alone could block PERK/eIF2α phosphorylation. We speculate that PPRV exploits eIF2α dephosphorylation to facilitate viral replication and PPRV P protein is involved in this molecular mechanism. This work provides new sights towards further understanding of PPRV pathobiology and its viral/host interactions.